Absorbed in Play and Gambling: Gadamer and Csíkszentmihályi - Csaba Olay (Critical Gambling Studies, 2022)
One of the most apparent features of playing and gambling is how easily people become engaged and absorbed into playing and gambling. In some cases, people lose themselves  in playing and gambling to the extent that addiction might occur. This paper seeks to contribute to the phenomenology of play and gambling by attempting to describe how and why playing and gambling are attractive for us, and how we get absorbed in playing or gambling. In doing so, I disregard the difference between play in a broader sense and gambling with whatever stakes where in the latter case the risk inherently belongs to the activity. To get a nuanced description, I focus on two prominent theories that clarify different aspects of the phenomenon of playing. First, Hans-Georg Gadamer’s analysis of play gives an account of how playing is like submerging into an independent reality. Second, I follow Mihály Csíkszentmihályi’s conception of meaningful activity which he called “flow”. The main interest of the paper will be the problem of what it means to enter and to indulge in the context of play, and how we come to immerse ourselves in the process of playing and gambling.